Steinalderliv på Helganes: Arkeologiske undersøkelser av en mellomneolittisk boplass i skjæringspunktet mellom nord og sør. Helganesprosjektet 2011–2013, Karmøy kommune, Rogaland (AmS-Varia, 2015)
In 2011, archaeological excavations were conducted at a middle Neolithic site on the outmost headland at Haugesund Airport on the island of Karmøy in Rogaland, Southwestern Norway. The excavations revealed three dwelling structures, a midden and a string of stones constructed to prevent the sea from flooding the living areas. The dwelling structures, defined as huts, consisted of several cultural layers with a depth up to 40 cm. Several fireplaces inside and outside the living areas were also uncovered. A total of 133 484 artefacts were recovered, including 515 shards of pottery, of which 122 shards were ornamented with corded stamps, pit imprints, bone imprints, zigzag ornamentation and knot winds. Of tools, there are fragments of ground flint adzes, and adzes and chisels of greenstone and other types of rock. Additional finds included many different forms of slate arrows, projectile points of type A, B and C, plate knifes of slate, greenstone and sandstone, and so on. The finds from the Helganes site have many parallels to other middle Neolithic sites in southern Norway. This publication gives an introduction to all the well-known dwellings from middle Neolithic A and B and compares them in terms of find inventory, 14C-dates and structures. This study concludes that there are many similarities between the sites which indicates social interaction along the coast of southern Norway and exchange of material culture, ideology and knowledge.